BIOCHEMICAL BONE MARKERS AS PREDICTORS OF BONE LOSSES FOLLOWING LIVER TRANSPLANTATION - V. P. Buzulina; I. A. Pronchenko; I. P. Yermakova; E. B. Yaroshenko; M. N. Kornilov; N. P. Shmerko (Вестник трансплантологии и искусственных органов)
24 recipients after ortotopic liver transplantation (9 women and 5 men) 18–57 years aged were studied in 1–2 and then through 4–18 months following operation. Bone mineral density (BMD) in repeated estimation in 13 recipients was elevated on 14 ± 10,5% and in 11 recipients was decreased on 2,5 ± 2,56%. BMD elevation was associated with bone remodelling normalization. BMD lowering followed transplant dysfunction, glucocorticoid therapy, bone resorption increasing and bone formation suppression.